Calciphylaxis: a literature review based in two case reports - Mendes,Marco (2014)
Calciphylaxis is a rare and devastating obliterative vasculopathy, leading to ischemia and subcutaneous necrosis. In most cases it affects patients with renal disease and is associated with high morbidity and mortality. We present two case reports followed recently in our department, and a literature review on this topic. Case one refers to an 80-year-old Caucasian woman with chronic kidney disease stage 5 and primary hyperparathyroidism with secondary brown tumour and calciphylaxis. Case two refers to a 59-year-old Caucasian woman admitted with severe nephrotic syndrome associated with amyloidosis, that developed a catastrophic picture of calciphylaxis, ending in the patients death. There is a critical need to understand the pathogenesis of calciphylaxis. Its comprehension is the only way to improve the survival of these patients, and may help to elucidate the pathophysiology of vascular calcification in general. Educating physicians in the prevention and early detection of calciphylaxis is crucial. Only by increasing the knowledge about risk factors, pathophysiology, response to treatment and outcome, will we be able to improve prophylaxis and therapy of patients with calciphylaxis, decreasing the high mortality of this entity.